The effects of a transcontinental flight on markers of coagulation and fibrinolysis in healthy men after vigorous physical activity. (7th February 2017) - Kupchak, Brian R.; Kraemer, William J.; Hooper, David R.; Saenz, Cathy; Dulkis, Lexie L.; Secola, Paul J.; Brown, Lee E.; Galpin, Andrew J.; Coburn, Jared W.; DuPont, William H.; Caldwell, Lydia K.; Volek, Jeff S.; et al.
ABSTRACT: Purpose : Athletes and military service members are known to undergo strenuous exercise and sometimes have to take long haul flights soon afterwards; however, its combined effect on many physiological functions is relatively unknown. Therefore, we examined the combined effects of a full-body muscle-damaging workout and transcontinental flight on coagulation and fibrinolysis in healthy, resistance trained men. We also determined the efficacy of a full-body compression garment in limiting their coagulation responses. Materials and Methods : Nineteen healthy, resistance trained men flew from Connecticut (CT) to California (CA), performed a full-body muscle-damaging workout and then flew back to CT. Ten participants wore full-body compression garments (FCG) for the duration of both flights and during all other portions of the study except during workouts and blood draws, when they wore loose clothing. Nine controls wore loose clothing (CON) throughout the study. Blood samples were collected at 16 h and 3 h before the initial flight from CT, immediately after landing in CA, immediately before and immediately after the full-body workout in CA, immediately after landing in CT, and at 29 h after landing in CT. Plasma markers of coagulation included activated partial thromboplastin time (aPTT), prothrombin fragment 1+2 (PTF 1+2) and thrombin ant-thrombin (TAT). Markers of the fibrinolytic system included the tissue plasmigen activator (tPA), plasminogen activator inhibitor-1 (PAI-1) and D-Dimer. Results : Both FCG and CON groups exhibited a faster aPTT after the full-body workout compared to all other time points. Thrombin generation markers, TAT and PTF 1+2, increased significantly after the full-body workout and immediately after landing in CT. Additionally, tPA increased after the full-body workout, while PAI-1 increased before the flight to CA, after the full-body workout, and just after landing in CT. The D-Dimer significantly increased after the full-body workout and at 29 h post-flight in both groups. Between groups, aPTT was significantly faster and TAT elevated with the CON group at 29 h post-flight. Also, PAI-1 demonstrated higher concentrations immediately after landing in CT for the CON group. Conclusion : A full-body muscle-damaging workout in conjunction with a trans-continental flight activated the coagulation and fibrinolytic systems. Additionally, wearing a full-body compression garment may limit coagulation following a workout through the recovery period.